Family Socioeconomic Status and Internalizing Problem Behavior Among Chinese Adolescents: The Chain Mediation Effect of Academic Performance and Peer Conflict - Wang, Yangyang; Xie, Tian; Xu, Jian (Frontiers in Psychology, 2022)
The study aims to provide a new perspective on understanding the relationship between family socio-economic status and internalizing problem behavior, and gives insights for fostering adolescent-parent relationships from a new perspective. Many studies have focused on the relationship between family socioeconomic status and internalizing problem behavior among adolescent of the adolescents, but research on the mechanisms of their roles is still lacking, and peer conflict has been ignored as the most important social relationship for adolescents. This study further identified two new mediating variables and a chain mediating mechanism model between them. Based on national longitudinal data from the China Family Panel Studies of wave 2018, 2467 adolescents at 10 to 15 were taken into analysis, and used macro PROCESS4.0 to examine the mechanism of Academic Performance and Peer Conflict in the relationship between Family socioeconomic status and Internalizing problem behavior. Main findings are：(1) Family SES significantly reduced peer conflict and internalizing problem behavior among the adolescents; (2) Adolescents who achieved better academic performance were less likely to involve in peer conflict; (3) Peer conflict mediated 30.41% of the relationship between family SES and adolescents' internalizing problem behaviors; (4) there existed a chain mediating mechanism, and the mediating effect of peer conflict was much stronger than the mediating effect of both academic performance and chain mediation pathways. This study is the first study to structure a chain mediation model to examine the role of academic achievement and peer conflict in the relationship between family SES and internalizing problem behavior. These findings have important implications in that it can provide adolescents with proper emotional de-escalation and peer conflict resolution, which is beneficial for adolescents' mental health during urban governance and rural development.